The communicative stance of CSR: reflections on the value of CSR communication. (3rd April 2017) - Golob, Ursa; Verk, Natasa; Ellerup-Nielsen, Anne; Thomsen, Christa; Elving, Wim J.L.; Podnar, Klement
Abstract : Purpose: The purpose of this paper is to introduce the third special issue on corporate social responsibility communication (CSRCom). In this editorial, the authors take the opportunity to share the latest knowledge, research and insights on CSRCom as presented at the third International CSR Communication Conference held in Ljubljana 17-19 September 2015. Design/methodology/approach: Many efforts have been made to map the research field of CSRCom. Two major ontological streams seem to stand out in CSRCom research: functionalism vs constructivism. In this editorial, the authors describe each of them, address the factors which contributed to their implementation within the CSRCom field and provide a rationale for bridging the two approaches. Findings: The papers selected for the issue demonstrate that recent studies of CSRCom are anchored both in functionalism and constructivism but that the attention towards using CSRCom in organisational processes of collaboration and networking is growing. This growth is aligned to the changes in the wider social environment. In this editorial, the authors are bridging both approaches and relating them to the most recent developments in CSR and CSRCom. Originality/value: This paper concludes that a growing body of empirical studies contributes to an increased understanding of how both functionalistic and constitutive perspectives are relevant and provide key insights for communication managers. It also accentuates the idea that the ability to expand the understanding of CSRCom from that of a means to an end to one, according to which communication represents an important end/goal in itself, that can play a crucial role in dealing with the growing complexity of CSR processes.